Ship Trajectory Extraction Using Python Vessel Tracking Interpolation Method - Widyadi Setiawan; Linawati Linawati; I Made Oka Widyantara; Dewa Made Wiharta; Sri Andriati Asri (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
A deep understanding of ship trajectory movements has essential implications for maritime applications, including navigation, monitoring, and marine traffic analysis. Efficient and accurate extraction techniques are necessary to extract valuable information from ship trajectory data. One commonly used approach is the interpolation method, which allows the reconstruction of smooth trajectories from recorded data points. This research is focused on analyzing the extraction of ship trajectories using the interpolation method provided by the Python Vessel Tracking (PyVT) library. This method allows interpolation of ship trajectory data based on various algorithms available in the library. This research aims to evaluate the effectiveness and accuracy of interpolation methods from PyVT in reconstructing ship trajectories from incomplete or disturbed data. Within this research's framework, several test scenarios were implemented to examine different types of ship trajectory data, including data with missing points and speed variations. Evaluation metrics RMSE (root mean Squared Error), which includes reconstruction accuracy, will be utilized from the interpolation algorithm in PyVT.